2007
DOI: 10.1001/archopht.125.12.1657
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and Adnexal Sarcoidosis

Abstract: To present the clinical features and management in a series of patients with orbital and adnexal sarcoidosis. Methods: This multicenter retrospective study included patients with biopsy-proven noncaseating granuloma involving the orbit or adnexa and evidence of systemic sarcoidosis. Clinical records were reviewed for initial examination findings, radiological findings, treatment modalities, and outcome. Results: The study included 26 patients (19 female, 7 male; mean age, 52 years). The most common feature at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
117
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 19 publications
3
117
0
2
Order By: Relevance
“…In larger case series, Mavrikakis et al, Demirci et al, and Prabhakaran et al reported partial or complete response to systemic corticosteroids in at least 95% of their patients with orbital and adnexal sarcoid [161][162][163], and recurrence rates were noted to be less than 10% [161,163].…”
Section: Sarcoidmentioning
confidence: 97%
See 2 more Smart Citations
“…In larger case series, Mavrikakis et al, Demirci et al, and Prabhakaran et al reported partial or complete response to systemic corticosteroids in at least 95% of their patients with orbital and adnexal sarcoid [161][162][163], and recurrence rates were noted to be less than 10% [161,163].…”
Section: Sarcoidmentioning
confidence: 97%
“…Ophthalmic sarcoidosis occurs frequently, and about 10% of these cases involve the orbit and ocular adnexa [160], with the lacrimal gland and orbit being the most frequently involved [161].…”
Section: Sarcoidmentioning
confidence: 99%
See 1 more Smart Citation
“…31 It as been documented that tear fi lm defi ciencies are common in sarcoidosis, even though clinical symptoms are present. In the same study, it was emphasized that defi ciency of mucin and lipid layers may also accompany aqueous layer defi ciency.…”
Section: Lacrimal Gland Infl Ammationmentioning
confidence: 99%
“…3 However, ocular manifestations of sarcoidosis may comprise a variety of clinical findings, including anterior, intermediate, or posterior uveitis, optic neuropathy, adnexal and orbital disease, scleral involvement, glaucoma, and cataracts. 4 The lacrimal gland is the most common adnexal site affected, 5 which can occur prior to other manifestations of the disease, 6 and may lead to subsequent sicca syndrome. Scleral involvement is infrequently reported in the literature, particularly in the absence of other ocular involvement.…”
mentioning
confidence: 99%